In the Nepalese context, can a husband's attendance during childbirth help his wife feel more in control of labour? - Sapkota Sabitri; Kobayashi Toshio; Kakehashi Masayuki; Baral Gehanath; Yoshida Istuko (BMC, 2012)
Abstract Background A husband's support during childbirth is vital to a parturient woman's emotional well-being. Evidence suggests that this type of support enables a woman to feel more in control during labour by reducing maternal anxiety during childbirth. However, in Nepal, where childbearing is considered an essential element of a marital relationship, the husband's role in this process has not been explored. Therefore, we examined whether a woman in Nepal feels more in control during labour when her husband is present, compared to when another woman accompanies her or when she has no support person. Methods The study participants were low risk primigravida women in the following categories: women who gave birth with their husband present (n = 97), with a female friend present (n = 96), with mixed support (n = 11), and finally, a control group (n = 105). The study was conducted in the public maternity hospital in Kathmandu in 2011. The Labour Agentry Scale (LAS) was used to measure the extent to which women felt in control during labour. The study outcome was compared using an F-test from a one-way analysis of variance, and multiple regression analyses. Results The women who gave birth with their husband's support reported higher mean LAS scores (47.92 ± 6.95) than the women who gave birth with a female friend's support (39.91 ± 8.27) and the women in the control group (36.68 ± 8.31). The extent to which the women felt in control during labour was found to be positively associated with having their husband's company during childbirth (β = 0.54; p < 0.001) even after adjusting for background variables. In addition, having a female friend's company during childbirth was related to the women's feeling of being in control during labour (β = 0.19; p < 0.001) but the effect size was smaller than for a husband's company. Conclusion The results show that when a woman's husband is present at the birth, she feels more in control during labour. This finding has strong implications for maternity practices in Nepal, where maternity wards rarely encourage a woman to bring her husband to a pregnancy appointment and to be present during childbirth.